Virtual art gallery tour: understanding the curatorial approach / Nur Muhammad Amin Hashim Amir, Hilal Mazlan and Aznan Omar - Hashim Amir, Nur Muhammad Amin; Mazlan, Hilal; Omar, Aznan (Universiti Teknologi MARA, Perak, 2022)
Virtual today is part of the new reality as the world starts to recognize its expediency. Virtual can branch out into multitudes of fields and usage with each one has its approach. Virtual tours in particular can be considered as one of the instruments capable of providing interactive elements in delivering mass access to information. The ease of accessibility is rather an opportunity than an option for anyone to explore. The purpose of this study is to understand the basic curatorial approach to organize a proper virtual gallery tour. Like its actual counterparts, the procedure is similar in many ways but with certain additional methodology. The research separates into three main curatorial stages mapping the actual gallery, constructing the virtual gallery, and publishing the tour. Each section discusses different methodologies which translate as a guideline to achieve that picture-perfect amalgamation. The research construes actual art exhibition as its plane of study to ensure that the evaluation is of the genuine result. The result is then assessed through its usability and accessibility for any interested individuals to practice. Conclusively, determine this research into providing a unification tool for any intuitional to organize their virtual gallery tour.